In silico search for and analysis of R gene variation in primitive cultivated potato species - A. A. Gurina; M. S. Gancheva; N. V. Alpatieva; E. V. Rogozina (Вавиловский журнал генетики и селекции)
Pathogen recognition receptors encoded by R genes play a key role in plant protection. Nowadays, R genes are a basis for breeding many crops, including potato. Many potato R genes have been discovered and found suitable for breeding thanks to the studies of a wide variety of wild potato species. The use of primitive cultivated potato species (PCPS) as representatives of the primary gene pool can also be promising in this respect. PCPS are the closest to the early domesticated forms of potato; therefore, their investigation could help understand the evolution of R genes. The present study was aimed at identifying and analyzing R genes in PCPS listed in the open database of NCBI and Solomics DB. In total, the study involved 27 accessions belonging to three species: Solanum phureja Juz. & Bukasov, S. stenotomum Juz. & Bukasov and S. goniocalyx Juz. & Bukasov Materials for the analysis were the sequencing data for the said three species from the PRJNA394943 and PRJCA006011 projects. An in silico search was carried out for sequences homologous to 26 R genes identified in potato species differing in phylogenetic distance from PCPS, namely nightshade (S. americanum), North- (S. bulbocastanum, S. demissum) and South-American (S. venturii, S. berthaultii) wild potato species, as well as the cultivated potato species S. tuberosum and S. andigenum. Homologs of all investigated protein-coding sequences were discovered in PCPS with a relatively high degree of similarity (85–100 %). Homologs of the Rpi-R3b, Rpi-amr3 and Rpi-ber1 genes have been identified in PCPS for the first time. An analysis of polymorphism of nucleotide and amino acid sequences has been carried out for 15 R genes. The differences in frequencies of substitutions in PCPS have been demonstrated by analysis of R genes, the reference sequences of which have been identified in different species. For all the studied NBS-LRR genes, the proportion of substituted amino acids in the LRR domain exceeds this figure for the NBS domain. The potential prospects of using PCPS as sources of resistance to Verticillium wilt have been shown.